Spinal cord injuries: the role of the nurse in their management - Mpouzika, Meropi; Karanikola, Maria (My University, 2005)
Spinal cord injuries constitute one of the major causes of permanent impairment and death for the young adults. Moreover, prehospital and hospital management (ER-ICU) of patients with spinal cord injury is crucial not only for their neurological prognosis but also for their survival. In the same time, nurses of the emergency department, as well as those of the intensive care unit have to take into consideration standard guidance and are also asked to manage multiple complications which involve spinal cord stabilization and acute care management. Spinal shock, neurogenic shock, orthostatic hypotension, respiratory insufficiency, bladder dysfunction, sexual dysfunction and autonomic hyperreflexia as well, are some of the main complications that can occur which depend on the type and level of injury. Nevertheless, for the patients with paraplegia and quadriplegia a collaborative interdisciplinary approach is required in order to achieve .the best expected outcomes with nurses to constitute an important member of that team.
Κακώσεις νωτιαίου μυελού : ο ρόλος του νοσηλευτή στην αντιμετώπιση τους
Keywords: Νursing management; Prehospital management; Quadriplegia; Paraplegia